Linda Carlson at Kimono exhibit - Unidentified photographer (Colorado State University. Libraries, 1990)
Photograph of Linda Carlson at the exhibition “Kimono,” held in the Gustafson Gallery from March 29 to May 31, 1990. One woman is facing towards Carlson. In the background, there are kimonos on display and another woman posing.
Keywords: Fashion -- History; Fashion -- Exhibitions